Greco-Roman and Jewish Tributaries to the New Testament Festschrift in Honor of Gregory J. Riley - Crawford, Christopher S. (Claremont Studies in New Testament and Christian Origins, 2018)
This volume examines the Greco-Roman and Jewish origins of and parallels to the thought in the New Testament.